Interactions Between Topological Defects and Nanoparticles - Do, Syou-P'heng; Missaoui, Amine; Coati, Alessandro; Resta, Andrea; Goubet, Nicolas; Royer, Sébastien; Guida, Geraldine; Briand, Emrick; Lhuillier, Emmanuel; Garreau, Yves; Babonneau, David; Goldmann, Michel; et al. (Frontiers in Physics, 2020)
Liquid Crystal (LC) topological defects have been shown to trap nanoparticles (NPs) in the defect cores. The LC topological defects may thus be used as a matrix for new kinds of NP organizations templated by the defect geometry. We here study composites of LC smectic dislocations and gold NPs. Straight NP chains parallel to the dislocations are obtained leading to highly anisotropic optical absorption of the NPs controlled by light polarization. Combining Grazing Incidence Small Angle X-ray scattering (GISAXS), Rutherford Back Scattering (RBS), Spectrophotometry and the development of a model of interacting NPs, we explore the role of the Np size regarding the dislocation core size. We use NPs of diameter D = 6 nm embedded in an array of different kinds of dislocations. For dislocation core larger than the NP size, stable long chains are obtained but made of poorly interacting NPs. For dislocation core smaller than the NP size, the disorder is induced outside the dislocation cores and the NP chains are not equilibrium structures. However, we show that at least half of these small dislocations can be filled, leading to chains with strongly enhanced electromagnetic coupling between the NPs. These chains are consequently more probably stabilized by the elastic distortions around the defect cores, the distortion being enhanced by the presence of the grain boundary where the dislocations are embedded.